Saxa loquuntur? Elasticity and capacity of age-old city churches (Bulletin KNOB, 2011)
Redesignation, wholly or partly, appears to be the magic charm to preserve church buildings. Consequently, attention has shifted from retrospective restoration to prospective intervention for contemporary uses. Most new interventions were designed as 'reversible' additions. The question is how much cultural elasticity churches have in order to bear the sometimes substantial interventions for the sake of exploitation without losing their power of expression as places of worship. Does it only concern the preservation of the 'speaking stones' or also the space in between or around them? Another question is whether the concept of 'compatibility', usually meant in a technical sense, can also be used in a wider sense for the assessment of the cultural-historical, functional and architectonic appropriateness of the interventions.These questions are explored on the basis of seven monumental churches which are more or less comparable to the Rotterdam Laurenskerk. For the new 'ministry' for Nieuwe Kerk in Amsterdam Cornelis Wegener Sleeswijk aimed at congruity in use of material (natural stone) and a timeless-traditional form language, but in 1980 this approach was criticized as being too historicizing. Pieterskerk in Leiden was redesignated as a multifunctional centre and restored for the second time in 2010. Consolidation, prevention of wear and tear and modest contemporary additions were the guidelines here. In 1984-1987 after a long search for a new use, Nieuwkerk in Dordrecht was converted into a combination of social hostel and supermarket after a design of Theo van Halewijn. This resulted in an intervention in which the conflict of interests between monument values and consumer values is inevitably expressed. Grote Kerk in Veere has had many functions. In spite of architectonic contrasts, the recent conversion (2004) into a music podium by Marx & Steketee was executed with more respect for the historical structure and more attention for coherence than in the French Period. The whole complex emanates a functional serenity which also does justice to the eventful history of the church. Kruisherenklooster and Kruisherenkerk (monastery and church) in Maastricht also went through many new functions. In 2004 the transformation into design hotel and restaurant was completed. Here architect's office Satijnplus entered into a creative competition with the monument. The result is spectacular, but not undisputed aesthetically.After the restoration of 1994, the tower of Eusebiuskerk in Arnhem, which was severely damaged during Operation Market Garden, was redesignated for hotel- and catering and tourist functions. A panoramic elevator was installed for this purpose (AGS architecten/Otis) contrasting in function and use of material with the historical substructure and running right across vaults and church bells. After the restoration (Van Hoogevest, 1979-1988) the Utrecht cathedral, Domkerk, was refurbished as 'Open Dom', inviting people to meet one another and be surprised. The tearoom was added in the side wing of the choir, projecting - as a compromise between present and past - into the cloister garth as a versatile bay window of metal and glass. After some discussion on the choice of material, this intervention was approved at the time because of the social objective and contemporary semi-transparent architecture. After a long period in which the maxims 'conservation takes precedence over renovation' and 'form follows function' dominated in the domain of preservation of monuments and historic buildings and of architecture, the current design assignment for architects in interventions is to create suitable links between old and new.